(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
Auditing is an essential part of ensuring transparency in joint operating contracts, as auditors assess compliance with agreed terms, verify the integrity of administrative and financial procedures, and ensure that all parties to the joint operating contract adhere to the approved laws and regulations, in addition to evaluating the distribution of revenues and expenditures in a manner that serves the public sector’s interests.Auditing reveals any violations or irregularities that may affect the rights of the parties participating in the operating contract, which enhances trust between the parties and contributes to improving transparency and fairness, in addition to discovering loopholes in the financial and administrative system, thus enabling the parties to address these issues early to avoid future disputes.The role of auditing is mainly based on verifying the validity of financial transactions, providing accurate reports on the financial position, and analyzing the effectiveness of internal control mechanisms. Auditing also enhances the application of best practices in managing joint operating contracts and ensures that procedures are in line with financial standards and local and international legislation. Ultimately, auditing plays a pivotal role in ensuring transparency in joint operating contracts, which enhances operational effectiveness and contributes to building an environment of trust between the participating parties, thus reflecting on the interests of the state’s public sector.